2017
DOI: 10.1016/j.apenergy.2017.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations of charging/melting cycles of paraffin in a novel shell and tube with longitudinal fins based heat storage design solution for domestic and industrial applications

Abstract: Due to vulnerability of solar energy based technologies to weather fluctuations and variations in solar thermal irradiance, thermal energy storage (TES) systems with their high thermal storage capacity offer a sustainable solution. In this article, experimental investigations are conducted to identify thermal performance of latent heat storage (LHS) unit in connection with flat plate solar collector during charging cycles. LHS unit is comprised of novel geometrical configuration based shell-andtube heat exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…To conduct charging cycles, the water supply is directed to pass through serpentine copper tubing in the solar collector, where steady radiant thermal energy from solar simulators is absorbed by the water. The technical specifications and operation details of the solar simulators based solar collector system is discussed comprehensively in [22,41], as presented in Table 1. The high temperature water at the solar collector outlet is directed to pass through the LHS tank, where heat transfer occurs between high temperature water in the tubes and paraffin in the shell container.…”
Section: Experimental Setup and Procedures 21 Experimental Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…To conduct charging cycles, the water supply is directed to pass through serpentine copper tubing in the solar collector, where steady radiant thermal energy from solar simulators is absorbed by the water. The technical specifications and operation details of the solar simulators based solar collector system is discussed comprehensively in [22,41], as presented in Table 1. The high temperature water at the solar collector outlet is directed to pass through the LHS tank, where heat transfer occurs between high temperature water in the tubes and paraffin in the shell container.…”
Section: Experimental Setup and Procedures 21 Experimental Setupmentioning
confidence: 99%
“…However, the literature lacks thermal evaluation of shell-and-tube heat exchangers with multi-tube passes and longitudinal fins with relatively higher thermal storage capacity to support integration into practical applications. Therefore, a novel geometrical configuration of a shell-and-tube heat exchanger with multi-tube passes and longitudinal fins was previously designed and optimised in [21], developed and experimentally examined for charging and discharging cycles in [22,23]. The experimental evaluations were focused on vertical and radial temperature distributions, and melting and solidification rates of paraffin in the proposed design solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was noticed that the optimised design under increasing inlet temperature from 50-70 o C significantly improved the phase transition rate and total enthalpy by 68.8% and 18.06%, respectively. Later on, the proposed novel design was experimented for series of charging and discharging cycles with connection to solar collector [14][15][16]. It was reported that the proposed design was capable of charging 14.35 MJ in 3 h and discharging 13.63 MJ in 1.5 h. Also, the mean charging and discharging powers were augmented by 69.71% and 36.05% with increasing temperature gradient.…”
Section: Introductionmentioning
confidence: 99%
“…This article aims to conduct a comprehensive numerical analyses on fourteen commercial metal-oxides based nano-PCM samples with three volume concentrations to evaluate their thermo-economic performance in shell and tube heat exchanger, which are neither considered in [13][14][15]28] nor reported in previous literature. Numerical model for nano-PCM include the effects of thermo-physical properties of base material and metal-oxides, nanoparticles size and volume concentrations, and operating temperature.…”
Section: Introductionmentioning
confidence: 99%